Proposed Organization of Family Cancer Clinics in Indonesia - Kunta Setiaji (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractAround 10-15% of breast cancers are associated hereditary and/or familial predisposition. By definition familial breast occurs in two or more first degree relatives within a nuclear pedigree (first or second degree relatives). Hereditary and familial cancer displays different characteristics in the pathological features, clinical course, response to treatment, and outcomes. Therefore, specific consultation and treatment need to be addressed to patients with hereditary or familial predisposition for example the need for rigorous surveillance and preventive treatment including options for preventive surgery. Cancer clinical genetic service is not yet formally available in daily clinical practice in Indonesia. Surgeons usually become the first medical specialist to see cancer patients with familial predisposition, therefore they have to elaborate clinical cancer genetic service under Family Cancer Clinic (FCC). Clinical genetic service within FCC consists of several step-wise tasks including assessment of personal and family history of cancer, personalized cancer risk assessment, review of medical and family history, individual cancer screening and surveillance recommendations, genetic testing if necessary, discussion of benefits and limitations of genetic test, cancer risk reduction options and preventive strategies, and opportunity to participate in research as well as clinical trial. Nation-wide network for FCC is of importance to share knowledge and skill to perform cancer genetic service. Ability to perform genetic test including the interpretation in Indonesia has also been required.